Plasma‐deposited AgOx‐doped TiOx coatings enable rapid antibacterial activity based on ROS generation. Issue 7 (31st January 2022) - Hegemann, Dirk; Hanselmann, Barbara; Zuber, Flavia; Pan, Fei; Gaiser, Sandra; Rupper, Patrick; Maniura‐Weber, Katharina; Ruffieux, Kurt; Ren, Qun
Abstract: To enable a rapid‐acting antibacterial mechanism without the release of biocidal substances, TiO2 catalysts have been considered based on the generation of reactive oxygen species (ROS). Doping with dissimilar metals generates electron‐hole pairs with narrow band gaps promoting the production of ROS. Here, plasma technology is investigated to deposit Ag nano islets on defective TiO x films, stabilized by plasma postoxidation suppressing Ag ion release. Importantly, ROS generation is maintained upon storage in the dark yet with diminishing efficacy; however, it can be restored by exposure to visible light. The rapid‐acting antibacterial properties are found to strongly correlate with ROS generation, which can even be maintained by functionalization with hydrophobic plasma polymer films. The cytocompatible coatings offer promising applications for implants and other medical devices. Abstract : The generation of reactive oxygen species (ROS) on plasma‐deposited AgO x /TiO x catalyst surfaces induces a rapid‐acting antibacterial effect within minutes in contact and in solution. Plasma oxidation yields Ag nano islet formation on defective TiO x coatings, stabilizing oxygen vacancies and avoiding Ag ion release. The catalytic effect based on redox reactions with adsorbed water and oxygen is maintained even during storage in the dark yet with diminishing efficacy; however, it can be restored during visible light exposure.